Modeling of battery pack sizing for electric vehicles - V. Sandeep; Suchitra Shastri; Arghya Sardar; Surender Reddy Salkuti (Institute of Advanced Engineering and Science, 2020)
The paper presents the mathematical modeling for battery pack sizing to evaluate the vehicle energy consumption by using the derivation from Parametric Analytical Model of Vehicle Energy Consumption (PAMVEC) by Simpson in R Studio. The assess of storage batteries for electric vehicles (EVs) application is presented in this paper. The main source of power in EVs are batteries and to properly optimize their use in them, a parametric vehicle dynamic model is created and factors like battery mass, energy needed for the EV etc. are predicted using inputs such as battery specific energy, range etc. An assessment of output parameters is performed by using different batteries and compared to determine best battery for EV application.